Proceedings of the 9th Asia Pacific Conference on Transportation &Amp; The Environment 2014
DOI: 10.31705/apte.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the implementation of bicycle lanes on Sri Lankan highways

Abstract: Bicycle lanes have become an integral part of the highway networks of many countries including Sri Lanka. They are encouraged as a pollution free, economic and healthy mode of transport throughout the world. So it is high time that a proper guideline for the same is introduced taking into account the local conditions of this country. Bicycle lanes are so far introduced to the road projects of Sri Lanka on ad hoc basis without consideration of the proper guidelines such as continuation of bicycle lanes on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Out of the two studies that have been carried out, a study based on Katubadda-Piliyandala cycling route identified barriers to cycling including design issues related to the cycling path where the non-connectivity of the cycling route, route being blocked by other vehicles, and other motor vehicles using the cycling path for transportation. [32] Another study of the Malabe-Kaduwela cycling route identified the issues related to cycling road design and some of the preferences of different potential user groups in Malabe for cycling promotion, which identified school children and university students as being more likely to consider cycling. This proposed bicycle promotion in contexts such as universities and schools.…”
Section: Recent Studies On Cycling In Sri Lankamentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the two studies that have been carried out, a study based on Katubadda-Piliyandala cycling route identified barriers to cycling including design issues related to the cycling path where the non-connectivity of the cycling route, route being blocked by other vehicles, and other motor vehicles using the cycling path for transportation. [32] Another study of the Malabe-Kaduwela cycling route identified the issues related to cycling road design and some of the preferences of different potential user groups in Malabe for cycling promotion, which identified school children and university students as being more likely to consider cycling. This proposed bicycle promotion in contexts such as universities and schools.…”
Section: Recent Studies On Cycling In Sri Lankamentioning
confidence: 99%
“…This proposed bicycle promotion in contexts such as universities and schools. [32] Previous studies could not identify planning issues for promoting cycling in Sri Lankan urban context, where under what conditions the modal transportation shift could be a success or why cycling promotion in Sri Lanka is lagging. However, sustainability is widely discussed in the planning process; therefore, it is essential to identify cycling barriers to plan better infrastructure.…”
Section: Recent Studies On Cycling In Sri Lankamentioning
confidence: 99%